2004
DOI: 10.4315/0362-028x-67.11.2450
|View full text |Cite
|
Sign up to set email alerts
|

Decontamination of Strawberries Using Batch and Continuous Chlorine Dioxide Gas Treatments

Abstract: Efficacy of chlorine dioxide (ClO2) gas in reducing Escherichia coli O157:H7 and Listeria monocytogenes on strawberries was determined using batch and continuous flow ClO2 gas treatment systems. Effects of continuous ClO2 gas treatment on total aerobic plate count, color, and residual ClO2 and chlorite on strawberries were also evaluated. Strawberries were spot inoculated with 7 to 8 log CFU per strawberry of each pathogen (E. coli O157:H7 and L. monocytogenes), stored for 1 day at 4 degrees C, and treated at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(48 citation statements)
references
References 13 publications
0
48
0
Order By: Relevance
“…Visual quality and freshness retain in tomato fruits by reducing respiration and ethylene production. Shelf life increased in ClO 2 gas treated strawberry fruits by reducing microorganism contamination (Han, Selby, Schultze, Nelson, & Linton, 2004) and, in tomato fruits, the risk of microbial activity was reduced (Trinetta, Morgan, & Linton, 2010). The shelf life of the control, 150 ppm NaOCl, 1 ppm ClO 2 gas 6 hours, 1 ppm ClO 2 gas 12 hours, 1 ppm ClO 2 gas 24 hours, 5 ppm ClO 2 gas 6 hours, and 5 ppm ClO 2 gas 12 hours -treated tomatoes amounted to 14,15,16,17,18,19, and 20 days at 5 ˚C, respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Visual quality and freshness retain in tomato fruits by reducing respiration and ethylene production. Shelf life increased in ClO 2 gas treated strawberry fruits by reducing microorganism contamination (Han, Selby, Schultze, Nelson, & Linton, 2004) and, in tomato fruits, the risk of microbial activity was reduced (Trinetta, Morgan, & Linton, 2010). The shelf life of the control, 150 ppm NaOCl, 1 ppm ClO 2 gas 6 hours, 1 ppm ClO 2 gas 12 hours, 1 ppm ClO 2 gas 24 hours, 5 ppm ClO 2 gas 6 hours, and 5 ppm ClO 2 gas 12 hours -treated tomatoes amounted to 14,15,16,17,18,19, and 20 days at 5 ˚C, respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…There are several advantages of using ClO 2 rather than hypochlorous acid (HOCl) such as ClO 2 's reduced reactivity with organic material, it has a greater activity at neutral pH, however; its stability may be problematic (Benarde, Snow, Olivieri, & Davidson, 1967). Han, Selby, Schultze, Nelson, and Linton (2004) investigated the use of ClO 2 gas treatments for the decontamination of strawberries and reported a 5 log reduction in microbial counts however, it is important to note that they also stated that the effectiveness of ClO 2 gas treatments for reducing pathogens varies for different types of produce. Lee, Costello, and Kang (2004) reported that E. coli O157:H7 inoculated on lettuce leaves were reduced by 3.4, 4.4, and 6.9 CFU/g after treatment of ClO 2 gas for 30 min, 1 h and 3 h, respectively.…”
Section: Introductionmentioning
confidence: 96%
“…This information seems to suggest i) that contrary to what has been documented for pathogenic microorganisms, it has been challenging to reduce populations of Botrytis cinerea using treatments with low concentrations of ClO 2 and ii) that despite Spotts et al and Roberts et al agreement on the concentration of the effective treatment (5 mg/L), the difference in exposure times (1 versus 10 min) implies that the biological subject where Botrytis cinerea is present has an effect on the efficacy of ClO 2 treatments. Strawberries are a unique fruit with irregular shape, seed-studded surfaces, and high organic acid content (Han, Selby, Schultze, Nelson, & Linton, 2004;Kallio, Hakala, Pelkkikangas, & Lapveteläinen, 2000). Moreover, their shelf life is short due to susceptibility to rotcausing pathogens and fast ripening due to high respiration rates (Kim, Kim, Lim, Jang, & Song, 2010).…”
Section: Introductionmentioning
confidence: 99%